Some Notes on the Acceleration Principle - Manne, A. S. (The Review of Economics and Statistics, 1945)
mHERE has been a growing tendency among economists to recognize the inadequacy of the simple acceleration principle as the explanation of investment activity. The qualifications and reservations that must be made for that principle to hold true in the real economic world have caused some economists to deny it virtually all validity. For instance, Professor Hansen says, is well known . . . that the simplified conditions usually assumed when the Principle of Acceleration is under discussion are rarely valid in the actual world. When more realistic assumptions are introduced, it is clear that the effect of new consumption upon investment is a very complex and uncertain one. 2 In this paper, the acceleration principle first will be set forth in its virginal simplicity. Then in Part II, the qualifications that theory suggests will be noted, and it will be seen how these are borne out by the statistics on investment in freight cars in the United States.3 Through these investigations, we hope to show that the acceleration principle does in large part serve to explain investment activity if additional variables are introduced and our theory is enlarged so as to include the effects of these variables. Since it has been dealt with so fully elsewhere,4 only a brief sketch of the so-called simple acceleration principle will be made. To put it most concisely, net investment is proportional to the rate of change of consumer-taking.5 Or, as J. M. Clark said, If demand be treated as a rate of speed at which goods are taken off the market, [demand for] maintenance varies roughly with the speed, but new construction depends upon the acceleration. 6 Another version of the doctrine is that the per cent changes in the stock of capital goods equal the per cent changes in the consumption of their products. This second version holds that in the first statement the constant of proportionality the constant of acceleration equals the amount of capital per unit of output the capital intensity. It is clear from the very outset that the abovestated theory is an over-simplification and that it does not describe the course of actual economic events. In Chart i the year-to-year per cent changes in the total number of freight cars are